Can artificial intelligence replace journalists? A theoretical approach - Cristian Londoño-Proaño; Jorge Buele (Frontiers in Communication)
In the digital age, journalism is facing significant transformations due to the impact of artificial intelligence, a technology that optimizes processes, but also poses ethical and technical dilemmas. This study addresses whether AI can replace journalists or whether it should be considered as a complementary tool that enhances their capabilities. The problem lies in the increasing automation of journalistic tasks and its impact on the quality, ethics and professional identity of the sector. The research justifies its relevance due to the need to understand the scope and limitations of this technology to guarantee ethical and contextualized journalism. The methodology adopted is qualitative and based on documentary analysis. Academic studies, technical reports, and case studies were reviewed to evaluate the use of AI in newsrooms, highlighting its capabilities in automation, personalization, and data analysis, along with its ethical and operational limitations. Among the main results, it is identified that artificial intelligence is effective for tasks such as automated news generation and massive data analysis, but its inability to perform critical analysis and ethical decisions limits it as a complete substitute for the journalist. Likewise, their dependence on trained data perpetuates biases that can compromise the credibility of information. This study highlights that artificial intelligence should be conceived as a support for the journalist, enhancing creativity and analytical depth without compromising the essential values of the profession. It also underscores the importance of a synergistic collaboration between technology and journalists, including regulation and training to take advantage of it ethically and effectively.